Multivessel Versus Culprit Vessel–Only Percutaneous Coronary Intervention Among Patients With Acute Myocardial Infarction: Insights From the TRANSLATE‐ACS Observational Study. Issue 10 (5th October 2017) - Ibrahim, Homam; Sharma, Praneet K.; Cohen, David J.; Fonarow, Gregg C.; Kaltenbach, Lisa A.; Effron, Mark B.; Zettler, Marjorie E.; Peterson, Eric D.; Wang, Tracy Y.
Abstract : Background: Among patients with acute myocardial infarction (MI) who have multivessel disease, it is unclear if multivessel percutaneous coronary intervention (PCI) improves clinical and quality‐of‐life outcomes compared with culprit‐only intervention. We sought to compare clinical and quality‐of‐life outcomes between multivessel and culprit‐only PCI. Methods and Results: Among 6061 patients with acute MI who have multivessel disease in the TRANSLATE‐ACS (Treatment With Adenosine Diphosphate Receptor Inhibitors: Longitudinal Assessment of Treatment Patterns and Events After Acute Coronary Syndrome) study, we used inverse probability‐weighted propensity adjustment to study the associations between multivessel and culprit‐only intervention during the index PCI and major adverse cardiovascular events, unplanned all‐cause readmission, and angina frequency at 6 weeks and 1 year. Multivessel PCI was performed in 1208 (20%) of patients with MI who had multivessel disease. Relative to the culprit‐only intervention, patients receiving multivessel PCI were similarly aged and more likely to be seen with non–ST‐segment elevation MI or cardiogenic shock. At 6 weeks, the initial multivessel PCI strategy was associated with lower major adverse cardiovascular events and unplanned readmission risks, whereas angina frequency was not significantly different between multivessel and culprit‐only PCI. At 1 year, major adverse cardiovascular event risk was persistently lower in the multivessel PCI group (adjusted hazard ratio, 0.84; 95% confidence interval, 0.72–0.99), whereas long‐term readmission risk (adjusted hazard ratio, 0.94; 95% confidence interval, 0.84–1.04) and angina frequency were similar between groups (adjusted odds ratio, 1.01; 95% confidence interval, 0.82–1.24). Similar associations were seen when patients with ST‐segment elevation MI and non–ST‐segment elevation MI were examined separately. Conclusions: Among patients with acute MI who have multivessel disease, multivessel PCI was associated with lower risk of all‐cause readmission at 6 weeks and lower risk of major adverse cardiovascular events at 6 weeks and 1 year. However, similar short‐ and long‐term angina frequencies were noted.